Development of the symmetrical laser shock test for weak bond inspection. (April 2019) - Sagnard, M.; Ecault, R.; Touchard, F.; Boustie, M.; Berthe, L.
Highlights: Laser induced shockwave to certify bonded assembly. No NDT currently available to assess bonded CFRP structures integrity. Detection capabilities of the S-LASAT to assess bond integrity of contaminated lab samples. Behaviour of both healthy and contaminated bonded CFRP under laser shock. Demonstration of the S-LASAT detection capabilities on real aircraft parts. Abstract: This study aims to assess the capability of the LAser Shock Adhesion Test to detect weak bonds in assemblies made of carbon fibre reinforced polymer laminates as well as understand the behaviour of different bonded composite structure under a shock load. A specific setup based on symmetrical laser shocks has been used. After each test, ultrasounds are used to determine if the bond has been damaged or not. At first, samples with two contaminants - de-icing fluid and finger prints - were studied. Then, the bond quality of two partially contaminated aircraft parts were investigated. These original results demonstrate the efficiency of the symmetrical laser shocks method as a Non-Destructive Test for bonded carbon fibre reinforced polymer assemblies.